Dispersed carbon cathodes for nonferrous metals extraction from technological waste waters - Zagorovsky, G. M.; Sidorenko, I. G.; Prikhod'ko, G. P.; Ogenko, V. M.; Gunyaev, A. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2001)
The processes of copper and nickel electrodeposition on the dispersed particles of thermoexpanded graphite and the conductive soot have been investigated with the cyclic voltammetry method. It was shown possibility of copper and nickel electrolytic extraction from the aqueous solutions of their salts with concentration 2 mg/dm3. Electrolysis in the reactor with dispersed three-dimensional flowing electrodes of the thermoexpanded graphite and the conductive soot showed posibility of nonferrous metals extraction to residual concentration lower than 0.1 mg/dm3, The characteristics of the electrochemical reactor for purification of the printed circuit cards manufacturing washing water with productivity 100 L per hour are adduced.